2013
DOI: 10.4103/2278-330x.114116
|View full text |Cite
|
Sign up to set email alerts
|

Conventional four field radiotherapy versus computed tomography-based treatment planning in cancer cervix: A dosimetric study

Abstract: Background:With advancements in imaging, wide variations in pelvic anatomy have been observed, thus raising doubts about adequate target volume coverage by conventional external radiotherapy fields based on bony landmarks. The present study evaluates the need for integrating computed tomography (CT)-based planning in the treatment of carcinoma cervix.Aims:To estimate inadequacies in target volume coverage when using conventional planning based on bony landmarks.Materials and Methods:The study consisted of 50 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…Present study was carried out on histopathological proven cancer cervix patients to assess the treatment outcome and toxicities receiving pelvic radiotherapy by two fi eld and four fi eld technique. In this study patients have been divided in two arms receiving radiation by two fi eld technique and four fi eld box technique as in reference studies done by Gupta et al 4 and Yamazaki et al 16 Enrolled patients in this study were of 30-75 years of age similar to the study conducted by Gulia et al 8 As in the study of Gupta et al the patients enrolled in our study were all squamous cell carcinoma histology. 4 The difference in the response achieved in the two groups was not found to be statistically signifi cant.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Present study was carried out on histopathological proven cancer cervix patients to assess the treatment outcome and toxicities receiving pelvic radiotherapy by two fi eld and four fi eld technique. In this study patients have been divided in two arms receiving radiation by two fi eld technique and four fi eld box technique as in reference studies done by Gupta et al 4 and Yamazaki et al 16 Enrolled patients in this study were of 30-75 years of age similar to the study conducted by Gulia et al 8 As in the study of Gupta et al the patients enrolled in our study were all squamous cell carcinoma histology. 4 The difference in the response achieved in the two groups was not found to be statistically signifi cant.…”
Section: Discussionmentioning
confidence: 93%
“…[5][6][7] AP-PA fi eld technique provides good coverage to the target volume whereas four fi eld box technique with parallel opposed AP-PA fi elds and two lateral opposed fi elds has better dose distribution leading to decrease normal tissue toxicity. 8 The most common technique for whole pelvic irradiation for cancer of the uterine cervix has been the AP-PA two-fi eld technique. However, the fourfi eld box technique has gained increasing acceptance.…”
Section: Bpkmch Nepalese Journal Of Cancer (Njc)mentioning
confidence: 99%
See 1 more Smart Citation
“…The study of 50 patients conducted at our own institute showed that in only 2 patients out of 50, was the whole of target volume encompassed by standard four field box. [24] This inadequacy in target volume coverage has significantly been overcome by the use of conformal techniques like 3DCRT and IMRT, as shown by the favorable outcome data from several institutional series. [9,10,[25][26][27] The most significant factor in IMRT planning is however, the standardization of consistent and accurate target volume definition.…”
Section: Discussionmentioning
confidence: 98%
“…However; from the study conducted at our institute, we found that in 48 out of 50 patients, the level of aortic bifurcation was above L4-L5 level and by keeping upper border according to conventional fields, median target volume miss at superior border of the fields was 2.95 cm and maximum was upto 7.27 cm. [24] When these patients were followed up clinically, it was found that three out of 50 patients developed local recurrence and three developed lymph node recurrences at a median duration of 6 mand all lymph node recurrences were outside the radiation field. On close evaluation, it was observed that in all, the level of aortic bifurcation was above L4-L5 junction.…”
Section: Ctv Nodal (Ctv 1)mentioning
confidence: 98%